Encapsulation and IR probing of cube-shaped octasilasesquioxane H8Si8O12 in carbon nanotubes. - Wang, J; Kuimova, M; Poliakoff, M; Briggs, G; Khlobystov, A (2006)
A spectroscopic probe of nanotube diameter: The strength of the interaction of H8Si8O12 with the inner walls of carbon nanotubes (see picture) depends on the inner diameter. This, in turn, affects the Si-H stretching frequency, which can be probed by IR spectroscopy. (Figure Presented). © 2006 Wiley-VCH Verlag GmbH and Co. KGaA.